2016
DOI: 10.1111/jfpp.12855
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermented Flaxseed Oil Cake of Improved Antioxidant Capacity as Potential Food Additive

Abstract: The influence of fermentation with Rhizopus oligosporus tempe mold (DSM 1964 or ATCC 64063 strain) on the antioxidant potential of flaxseed oil cake was studied. Solid-state fermentation (SSF) process resulted in the slight increase in proteins and the significant loss of lipids. Even 48 h, the shortest fermentation period, caused the significant increase in phenolic content (13-85%), radical scavenging activity (about twofold higher against DPPH • ) and reducing power (by 20-30%). Prolongation of the fermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…The prolongation of the incubation time (up to 72 and 96 h) did not further improve the activity of the material, and it even had the opposite effect in the case of two strains (RP 0.5 values increased by over 30% (DSM 1964) and over 70% (ATCC 64063), as compared to the material fermented for 48 h). This tendency is different than the one observed during the fermentation of flaxseed oil cake with ATCC 64063 and DSM 1964, where the longer incubation time (72 h-144 h) was generally more effective than a two-day process [19].…”
Section: Effect Of the Processingcontrasting
confidence: 87%
See 3 more Smart Citations
“…The prolongation of the incubation time (up to 72 and 96 h) did not further improve the activity of the material, and it even had the opposite effect in the case of two strains (RP 0.5 values increased by over 30% (DSM 1964) and over 70% (ATCC 64063), as compared to the material fermented for 48 h). This tendency is different than the one observed during the fermentation of flaxseed oil cake with ATCC 64063 and DSM 1964, where the longer incubation time (72 h-144 h) was generally more effective than a two-day process [19].…”
Section: Effect Of the Processingcontrasting
confidence: 87%
“…The effect of tempe-type fermentation on the˙OH scavenging ability of plant materials (flaxseed oil cake, quinoa seeds, buckwheat groats) observed in our earlier experiments was positive [19][20][21]. However, the prolongation of the incubation (up to 144 h) was not effective in the case of flaxseed oil cake fermentation with R. oligosporus DSM 1964 and ATCC 64063 [19]. A result similar to the one observed in the present study was previously reported for sugared black tea fermented with kombucha ('tea fungus'-a symbiotic association of acetic acid bacteria and yeasts), where the˙OH-scavenging activity decreased, while the DPPH˙-scavenging activity increased as a result of biotreatment [22].…”
Section: Effect Of the Processingmentioning
confidence: 52%
See 2 more Smart Citations
“…It can also be applied as an alternative method for the utilisation of plant by-products. Our previous research showed that the application of R. oligosporus DSM 1964 and ATCC 64063 cultures in the processing of fl axseed oil cake may result in products with enhanced soluble phenolic content and increased antioxidant activity, suitable as functional food additives (17).…”
Section: Introductionmentioning
confidence: 99%